The Unique Positive Solution for Singular Hadamard Fractional Boundary Value Problems. (20th June 2019) - Mao, Jinxiu; Zhao, Zengqin; Wang, Chenguang
Abstract : In this paper, we investigate singular Hadamard fractional boundary value problems. The existence and uniqueness of the exact iterative solution are established only by using an iterative algorithm. The iterative sequences have been proved to converge uniformly to the exact solution, and estimation of the approximation error and the convergence rate have also been derived.